ZmCOL3, a CCT gene represses flowering in maize by interfering with the circadian clock and activating expression of ZmCCT. Issue 6 (14th March 2018) - Jin, Minliang; Liu, Xiangguo; Jia, Wei; Liu, Haijun; Li, Wenqiang; Peng, Yong; Du, Yanfang; Wang, Yuebin; Yin, Yuejia; Zhang, Xuehai; Liu, Qing; Deng, Min; et al.
Abstract: Flowering time is a trait vital to the adaptation of flowering plants to different environments. Here, we report that CCT domain genes play an important role in flowering in maize ( Zea mays L.). Among the 53 CCT family genes we identified in maize, 28 were located in flowering time quantitative trait locus regions and 15 were significantly associated with flowering time, based on candidate‐gene association mapping analysis. Furthermore, a CCT gene named ZmCOL3 was shown to be a repressor of flowering. Overexpressing ZmCOL3 delayed flowering time by approximately 4 d, in either long‐day or short‐day conditions. The absence of one cytosine in the ZmCOL3 3'UTR and the presence of a 551 bp fragment in the promoter region are likely the causal polymorphisms contributing to the maize adaptation from tropical to temperate regions. We propose a modified model of the maize photoperiod pathway, wherein ZmCOL3 acts as an inhibitor of flowering either by transactivating transcription of ZmCCT, one of the key genes regulating maize flowering, or by interfering with the circadian clock. Abstract : This study emphasizes the important roles of CCT gene family in maize flowering time. One of them, ZmCOL3, was validated to be a repressor of flowering time, and its role was integrated into a modified model for the maize photoperiod pathway.